Innovative microbial strategies in atopic dermatitis - Jingtai Ma; Jingtai Ma; Yiting Fang; Yiting Fang; Jinxing Hu; Shiqi Li; Lilian Zeng; Siyi Chen; Zhifeng Li; Ruiling Meng; Xingfen Yang; Fenglin Zhang; et al. (Frontiers in Immunology)
Atopic dermatitis (AD) is characterized by chronic and recurrent itching with a high burden of disability-adjusted life years (DALYs, a measure of overall disease burden). Traditional treatments mainly include corticosteroids, which have a good effect on controlling inflammation but adverse side effects. Recently, advancements in understanding the pathogenesis of AD have led to the emergence of a variety of novel therapeutic approaches, such as microbiome manipulation, offering renewed hope for more effective management of this condition. These strategies are particularly promising for mild-to-moderate AD, where dysbiosis and immune imbalance (e.g., Th2 skewing) are key drivers, though some approaches (e.g., fecal microbiota transplantation) are being explored for refractory cases. It has been shown that microbiome manipulation has the potential to improve disease states and regulates the balance of the inflammatory system in a variety of ways. Various approaches have been preclinically and clinically tested, including probiotics (and multiple co-applications), prebiotics, postbiotics, unmethylated CpG motifs, fecal microbiota transplantation, herbal fermentation technology with microorganisms and phage. In this review, we discuss these microbiome manipulation methods and emphasizes the potential of microbiome-based interventions to modulate Th1/Th2 balance with fewer side effects, ultimately leading to control of inflammation in AD. Further translational research in this field is needed to integrate when we apply this therapy and the capability for disease treatment and prevention.